2022
DOI: 10.2497/jjspm.69.99
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Proton Conductivity of the Mixed Cation Phosphate, KCo<sub>1−<i>x</i></sub>H<sub>2<i>x</i></sub>(PO<sub>3</sub>)<sub>3</sub> • <i>y</i>H<sub>2</sub>O with a with a One-dimensional Tunnel Structure

Abstract: A mixed cation phosphate, KCo 1−x H 2x (PO 3 ) 3 • yH 2 O, with a tunnel structure was synthesized by a coprecipitation method and investigated as a proton conductor. KCo 1−x H 2x (PO 3 ) 3 • yH 2 O formed a solid solution in the range of x = 0-0.18, and the enhancement of the absorption peaks corresponding to the vibration and stretching modes of OH and POH were observed for increasing x. The sample with x = 0.18 exhibited a high proton conductivity in the temperature range of 25-250°C, and the value of 2.6 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The conductivity of KNi 1– x H 2 x (PO 3 ) 3 ·y H 2 O improved with the proton content. The proton conductivity increased from room temperature to 200 °C and decreased slightly above 225 °C due to the desorption of water of crystallization, which is a similar feature to other tunnel phosphates. The highest conductivity value of 1.7 × 10 –2 S cm –1 was obtained at 275 °C for the sample with x = 0.18. The electronic conductivity value, σ e , at x = 0.18 obtained from the DC measurement was in the order of 10 –6 S cm –1 , as shown in Figure S4, close to the measurement limit of the instrument.…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…The conductivity of KNi 1– x H 2 x (PO 3 ) 3 ·y H 2 O improved with the proton content. The proton conductivity increased from room temperature to 200 °C and decreased slightly above 225 °C due to the desorption of water of crystallization, which is a similar feature to other tunnel phosphates. The highest conductivity value of 1.7 × 10 –2 S cm –1 was obtained at 275 °C for the sample with x = 0.18. The electronic conductivity value, σ e , at x = 0.18 obtained from the DC measurement was in the order of 10 –6 S cm –1 , as shown in Figure S4, close to the measurement limit of the instrument.…”
Section: Resultsmentioning
confidence: 51%
“…Although the positions of the protons in the crystal structure could not be determined in this study, the FTIR spectra suggested that they were located between the PO 4 tetrahedra and the oxygen of the crystal water, the same as other tunnel phosphates. Since PO 4 tetrahedra tend to form P–O–H bonds with protons, phosphates with the structure of connected PO 4 tetrahedra would have induced an adjacent arrangement of crystal water in the open framework. The distances of K–O(4) and K–O(5) were 2.52 and 2.62 Å, respectively.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations